Inhibition of Inositol Phosphorylceramide Synthase by Aureobasidin A in Candida and Aspergillus Species - Zhong, Wenyan (American Society for Microbiology, 2000)
Inositol phosphorylceramide (IPC) synthase is an enzyme common to fungi and plants that catalyzes the transfer of phosphoinositol from phosphatidylinositol to ceramide to form IPC. The reaction is a key step in fungal sphingolipid biosynthesis and the target of the antibiotics galbonolide A, aureobasidin A, and khafrefungin. As a first step toward understanding the antifungal spectrum of IPC synthase inhibitors, we examined the sensitivity of IPC synthase to aureobasidin A in membrane preparations of Candida species (Candida albicans, C. glabrata, C. tropicalis, C. parapsilosis, and C. krusei) and Aspergillus species (Aspergillus fumigatus, A. flavus, A. niger, and A. terreus). As expected, preparations from the five Candida species, all exquisitely susceptible to aureobasidin A (MICs, <2 μg/ml), had IPC synthase activity (specific activity, 50 to 400 pmol/min/mg of protein) sensitive to aureobasidin A (50% inhibitory concentrations [IC(50)s], 2 to 4 ng/ml). Surprisingly, preparations from the four Aspergillus species, including A. fumigatus and A. flavus, which are intrinsically resistant to aureobasidin A (MICs, >50 μg/ml), had IPC synthase activity (specific activity, 1 to 3 pmol/min/mg of protein) also sensitive to aureobasidin A (IC(50)s, 3 to 5 ng/ml). The mammalian multidrug resistance modulators verapamil, chlorpromazine, and trifluoperazine lowered the MIC of aureobasidin A for A. fumigatus from >50 μg/ml to 2 to 3 μg/ml, suggesting that the resistance of this major fungal pathogen is the result of increased efflux.